Expandable table from wooden pallet / Ahmad Safwan Kamaruzaman - Kamaruzaman, Ahmad Safwan (Faculty of Applied Sciences, 2018)
In this study, the expandable table was designed and produced by using wooden pallet (pine species). The design is more focus on saving space and multipurpose. Effective space saving does not depend on downscaling, but on smart ways of collapsing a piece of furniture or making it more collapsible. After expandable table has been produced, the survey was undertaken in evaluating customer feedback on the characteristic of product by distributing a set of questionnaires to 100 correspondents in UiTM Jengka and Bandar Pusat Jengka, Pahang. There were a few issues have been analysed such as raw material, design and marketing. A set of questionnaire was distributed to 100 respondents of different gender, profession, income and age. The characteristics evaluated by the respondents include material of this expandable table, design and marketing. The study aims to evaluate customer feedback on the saving space design and multipurpose design